Morfologi dan Kelimpahan Mikroplastik pada Sungai Mati, Bali - Utami, Ratu Dhyan; Perwira, Ima Yudha; Saraswati, Ni Luh Gede Rai Ayu (Bumi Lestari; Vol 25 No 1 (2025)DO - 10.24843//blje.2025.v25.i01.p01, 2025)
Microplastics are plastic particles that are >5 mm in diameter and are most often found on the surface of river water. This study aims to determine the morphology (size, type, and color) and abundance of microplastics in Mati River, Bali. This research was conducted in June - July 2024. Water samples were taken at 3 stations, namely on the right, center, and left side. This study used a purposive sampling method. Observation of microplastics using a stereo microscope with a size of 0.7× and 4.5× with the help of ImageJ software. The most common sizes found at each station were <0.5 mm to 1-3 mm and the lowest size was ?5 mm. The dominant type is Fiber. There are 8 types of colors found, namely: black, red, green, blue, brown, white, yellow, and clear. The most common color seen in 3 stations was black. The abundance of microplastics at each station is shown in Station 1 which is 1.20 particles/liter, station 2 which is 0.90 particles/liter, and Station 3 which is 1.30 particles/liter. Keywords: Water; Microplastics; Dead River